On the origin of Hobbes’ conception of language : the literary culture of English renaissance humanism (2012)
ABSTRACT: Hobbes’ education in the literary culture of English Renaissance humanism has been overlooked as an important tradition in understanding his position in Early Modern Philosophy. Against the traditional readings of Hobbes’ conception of language as a sequel to Medieval nominalism, I will argue that Hobbes’ education in the literary culture of Renaissance humanism and his subsequent developments in this tradition would have allowed him to consider philosophical problems raised by new science in an original way and, thus, to introduce his innovative conception of language as the core of his solution to the problem of social and natural orders.